A numerical efficient splitting method for the solution of HIV time periodic reaction-diffusion model having spatial heterogeneity - Raza, Nauman; Arshed, Saima; Bakar, Abu; Shahzad, Aamir; İnç, Mustafa (Elsevier, 2023)
This study examines a novel reaction-diffusion model for the existence and treatment of acquired immunodeficiency syndrome. This model is a spatial extension of the recent HIV model and human immunodeficiency viruses cause this disorder. The most significant barrier to eradicating this virus is latency and the virus' subsequent viral reservoir in CD4+ T cells. A nonstandard operator splitting strategy is proposed to approximate the solution of the time-periodic reaction-diffusion model. The main advantages of employing this approach over other techniques are its low computational costs, high accuracy and ease of implementation. The results are truly solid and match those available in the literature. The nature of the solution for the threshold parameter is demonstrated graphically using numerical results. Finally, the M-matrix theory and the positivity of the proposed scheme are discussed.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: HIV; Reaction-diffusion model; Basic reproduction number; Nonstandard operator splitting method; Positivity